Interaction of high density lipoprotein particles with membranes containing cholesterol - Sanchez, Susana A. (2007)
In this study, free cholesterol (FC) efflux mediated by human HDL was investigated using fluorescence methodologies. The accessibility of FC to HDL may depend on whether it is located in regions rich in unsaturated phospholipids or in domains containing high levels of FC and sphingomyelin, known as "lipid rafts." Laurdan generalized polarization and two-photon microscopy were used to quantify FC removal from different pools in the bilayer of giant unilamellar vesicles (GUVs). GUVs made of POPC and FC were observed after incubation with reconstituted particles containing apolipoprotein A-I and POPC [78Å diameter reconstituted high density lipoprotein (rHDL)]. Fluorescence correlation spectroscopy data show an increase in rHDL size during the incubation period. GUVs made of two "raft-like" mixtures [DOPC/DPPC/FC (1:1:1) and POPC/SPM/FC (6:1:1)] were used to model liquid-ordered/liquid-disordered phase coexistence. Through these experiments, we conclude that rHDL preferentially removes cholesterol from the more fluid phases. These data, and their extrapolation to in vivo systems, show the significant role that phase separation plays in the regulation of cholesterol homeostasis.